Suplementação de aminoácidos para suínos castrados e inteiros em crescimento e terminação: desempenho e custo da alimentação - Porolnik, Glauber Valentim (2010)
The objective of this dissertation was to evaluate the performance and feed costs of barrows and boars fed amino acid supplemented diets. Forty-eight animals with initial live weight of 38.8 ± 0.2kg were distributed in a randomized block design with three treatments, barrows of high production (CM), boars (IM) fed a diet of castrated male high production and IM supplemented with 5% of amino acids (IM+5%AA). They were evaluated over a forty-seven day period where three diets were used, growing diets (1 and 2) and a finishing diet. The treatments had no effect (P>0.05) on animal body weight and weight gain. Feed intake, feed conversion ratio and feed cost were different (P<0.05) among treatments. Average feed conversion was 2.43kg, the conversion observed on CM (P<0.05) was higher at 5.5 and 5.2% when compared to IM and IM+5%AA, respectively. Feed conversion ratio was 2.28, and the CM showed higher conversion (P<0.05) at 6.2 and 11.6% for IM and IM+5%AA, respectively. Average feed cost was R$ 1.82/kg, being higher (P<0.05) for CM (P<0.05) 6.2 and 8.9% in relation to IM and IM+5%AA respectively. The sex category (barrows or boars) and amino acid supplementation did not affect live body weight and weight gain, but did however, alter the feed intake, feed conversion ratio and feed cost.